الذكاء اللغوي والذكاء الاجتماعي وعلاقتهما بالتحصيل في المواد الدراسية الأساسية لتلاميذ التعليم الابتدائي - موساوي, فرحات; قنوعة, عبد اللطيف (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت هذه الدراسة إلى الكشف عن العلاقة بين نوعين من الذكاءات المتعددة وهما الذكاء اللغوي والذكاء الاجتماعي بالتحصيل في المواد الدراسية الأساسية (اللغة العربية، الرياضيات، الفرنسية) لتلاميذ التعليم الابتدائي، حيث تم استخدام المنهج الوصفي والاعتماد على النسخة المعرّبة لمقياسيّ الذكاء اللغوي والذكاء الاجتماعي المأخوذين من قوائم غاردنر للأطفال في سن المدرسة والتي ترجمها محمد (2006) وأيضا نتائج الاختبارات التحصيلية للمواد المعنية الخاصة بالفصل الأول للموسم الدراسي 2021/2022 ، وقد شملت عينة الدراسة 73 تلميذا من مدرستي غانية أحمد وأبو بكر الصديق بالبياضة، وبعد تحليل البيانات بواسطة نظام الحزمة الإحصائية أس بسس ، وباستخدام الأسلوب الإحصائي بيرسون، أظهرت نتائج الدراسة أنه توجد علاقة ذات دلالة إحصائية بين الذكاء اللغوي والتحصيل في المواد الأساسية، وأيضا توجد علاقة ذات دلالة إحصائية بين الذكاء الاجتماعي والتحصيل في مادة اللغة العربية، بينما لا توجد علاقة ذات دلالة إحصائية بين الذكاء الاجتماعي والتحصيل في كل من مادتي الرياضيات والفرنسية. Abstract: This study aims at revealing the relationship between multiple intelligences (linguistic and social) and academic achievement in basic subjects (Arabic, Mathematics, and French) for primary education in elementary school. The linkage-descriptive method was used, and it relied on the Arabized version of the linguistic and social intelligence tests taken from Gardner's lists of school-age children translated by Mohammed (2006) as well as the results of the summative tests of the relevant subjects for the first semester of the 2021/2022. The study sample consisted of 73 pupils. from both schools ghania ahmed and abubakre sedik bayada, After doing the data analysisby the SPSS Statistics and using the Pearson statistical method, the results of the study show that there is a statistically significant relationship between linguistic intelligence and academic achievement in basic materials. Results also show a statistically significant relationship between social intelligence and academic achievement in the subject of Arabic. However, it has been shown that there is no statistically significant correlation between social intelligence and pupils' academic achievement in both mathematics and French.
مقال
Keywords: الذكاءات المتعددة، الذكاء اللغوي، الذكاء الاجتماعي، التحصيل الدراسي، المواد الدراسية; Multiple Intelligences. Linguistic Intelligence, Interpersonal Intelligence, academic achievement, school subjects